Ethics of Archival Practice: New Considerations in the Digital Age - Hamer, Alyssa (Archivaria, 2018)
Archivists’ work has always involved an inherently ethical praxis, and now is on the brink of a tipping point: in the very near future, archives professionals will begin to accession greater numbers of digital records than paper ones. How will the complexities of the digital environment influence traditional approaches to selection, preservation, and access? In this paper, contemporary discourse related to the digital shift will be examined, both in terms of archival functions related to the management of digital records, as well as broader issues concerning government accountability, privacy rights, big data, and large-scale archiving. Beginning with an assessment of the current ethical codes set out by major archival associations and their capacity to address new considerations presented by the digital shift, this paper then examines several of the more insidious impacts brought about by the creation and management of digital and born-digital records. Through this analysis, it becomes clear that today’s archival practitioners must call for greater professional guidance and openness in relation to these modern challenges, and must seek out opportunities to showcase their specialized knowledge in the interests of preserving the reliability, authenticity, and completeness of the historical record for future generations. RÉSUMÉ Le travail des archivistes a toujours comporté une praxis éthique inhérente et se trouve maintenant à un point critique : dans un avenir très proche, les professionnels des archives vont commencer à recevoir un plus grand nombre de documents numériques que de documents sur papier. Comment les complexités de l’environnement numérique influenceront-elles les approches traditionnelles à la sélection, à la préservation et à l’accès? Dans ce texte, on examinera le discours contemporain par rapport à la transition numérique, tant en termes de fonctions archivistiques liées à la gestion des documents numériques, qu’en ce qui a trait aux questions plus vastes de l’imputabilité du gouvernement, des droits à la vie privée, des mégadonnées et de l’archivage à grande-échelle. En partant d’une évaluation des codes d’éthiques courants établis par les principales associations archivistiques et de leur capacité à faire face aux nouvelles considérations soulevées par la transition numérique, ce texte examine ensuite plusieurs autres effets insidieux qui découlent de la création et de la gestion des documents numériques et des documents créés numériquement. De par cette analyse, il devient évident que les praticiens en archivistique d’aujourd’hui doivent exiger davantage d’orientation professionnelle et d’ouverture face à ces défis modernes et doivent chercher de nouvelles occasions de mettre en évidence leur connaissances spécialisées dans le but de préserver la fiabilité, l’authenticité et l’intégralité du document d’archives historique pour les générations futures.